Reconstructing the Notion of Nationalism: Conversations About Women and Nationalism - Aprilia, Iqraa Runi; Rahayu, Ruth Indiah (Jurnal Perempuan, 2018)
Contemporary feminists in Indonesia do not yet have questions about nationalism, since the conversation about nationalism has been considered final at the beginning of Indonesian independence. In fact, in terms of contemporary analysis, women have problems with nationalism, when the definition of nationalism is dominated by the study of political science that is male-view biased. By tracing history to contemporary time, the relationship between women and nationalism is dominated by patriarchal interests for the mobilization of power, even if women have an independent political interest. That is why political interests of women are situated marginally in nationalism. But if we use the perspective of the social sciences, as feminist theories, then the notion of nationalism is broader than that of women and the state. We are still less productive in abstracting the relationship between women and citizens in nationalism, while it is a daily practice of women’s struggles both personally and organically. Women have proven to be an active agency to become citizens beyond the mobilization of the state. This paper seeks to arouse feminist questions about nationalism, in order to reveal the role of women who are hidden in nationalism.